Psychology for prospective teachers in Primary Education: yes, but which one? Exploratory analysis of Psychology subjects in Initial Teacher Training programs in Chile (Revista INTEREDU11, 2021)
This article presents the results of an exploratory study around training in psychology subjects in future Primary-education teachers. This study sought to problematize the degree of learnings and pedagogical-practices’ real needs, in contrast to what the regulations establish for the initial teaching training, starting from a review analysis of nine psychology subject in four different Pedagogy-for-primary-Education programs, plus a survey applied to graduates from such career. The data collected was analyzed by using descriptive categories, and the programmes were compared with the regulations, the theory, and what answers from the survey respondents. The results revealed just a slight approach to psychology and only shallow application into practice, as well as absence or little presence of topics related to it, such as selfcare, social behavior, and proper manners.